IDENTIFYING FACTORS AFFECTING WAITING TIMES IN EMERGENCY INSTALLATION AT A PRIVATE HOSPITAL IN MALANG: TIME MOTION STUDY - agus, Muharami; djauhari, thantowi; Putra, Kuswantoro Rusca (Universitas Brawijaya, 2025)
Emergency Installation (IGD) is the main point of entry for patients to the hospital. Prolonged IGD waiting time. may lead to crowding that results in patients’ complaints, patient safety incident, and decrease in the quality of service. Waiting time starts from triage to when the patient is transferred to the hospital room with the standard waiting time set < 6 jam. The research aimed at identifying what factors dominantly affected prolonged IGD waiting time in Hospital X. The descriptive research, conducted in a private hospital in Malang Regency, used Time and Motion Study. The sample was collected using simple random sampling technique and included 50 IGD patients that met Emergency Safety index (ESI) 1, 2, dan 3 category. The result revealed that the average waiting time of ESI 1, ESI 2 and ESI 3 patients was 5 hours. There were 12 patients (24%) with waiting time longer than 6 hours. Partial referral for CT scan, delayed patient transfer due to the wait time for result of consultation with attending physician, stabilization of patients, and unavailable hospital rooms were identified as contributing factors to prolonged IGD waiting time.